2007
DOI: 10.2169/internalmedicine.46.6238
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Formation of Aspergillus mycetoma in a Patient Receiving Corticosteroid Treatment. Serial Radiographic Observation Over Two Months

Abstract: This study presents the case of rapidly progressing pulmonary aspergillosis in a 47-year-old

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Aspergillosis is well known in a patient with perinuclear Antineutrophilic Cytoplasmic Antibody (p-ANCA)-associated vasculitis and pulmonary renal syndromes [1]. However, only a few cases have been reported in AN-CA-associated patients.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Aspergillosis is well known in a patient with perinuclear Antineutrophilic Cytoplasmic Antibody (p-ANCA)-associated vasculitis and pulmonary renal syndromes [1]. However, only a few cases have been reported in AN-CA-associated patients.…”
Section: To the Editormentioning
confidence: 99%
“…However, only a few cases have been reported in AN-CA-associated patients. Akimoto, et al reported a patient of ANCA-associated vasculitis with corticosteroid therapy who had massive recurrent hemoptysis due to pulmonary Aspergillus mycetoma [1]. A disseminated aspergillosis with invasion of the lungs, heart, and brain developed following resolution of pneumocystis pneumonia in a patient receiving long-term prednisolone therapy for Good-pasture syndrome with positive ANCA, an autoimmune disease that attacks the lungs and kidneys [2].…”
Section: To the Editormentioning
confidence: 99%
“…The cavity can then be colonised by Aspergillus species to form an aspergilloma. In such cases aspergilloma formation is thought to be accelerated by corticosteroids [16].…”
Section: Association Of Pulmonary Aspergilloma and Allergic Bronchopumentioning
confidence: 99%
“…Rapid development of an aspergilloma within a 2-month period was reported in a 47-yr-old female who had cavitary disease for 7 yrs due to tuberculosis. This occurred after she was prescribed corticosteroids for pulmonary-renal syndrome due to systemic vasculitis [32].…”
mentioning
confidence: 99%